2016
DOI: 10.4236/ijmpcero.2016.54029
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dual-Energy Computed Tomography for Breast Cancer Diagnosis

Abstract: The present study aimed to investigate the possibility of using dual-energy computed tomography (CT) before therapy to discriminate between normal breast tissue and tumor tissue in patients with breast cancer, without the need to use a contrast medium. The following patient data were extracted by interview and from the hospital's radiology information system: height, weight, age, menstrual cycle, CT images of normal tissue and tumors with or without contrast medium, and the histopathological diagnosis of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Thus, the present study aimed to evaluate the utility of contrast-enhanced DECT for visualizing and evaluating an IC of breast cancer. Some previous studies have focused on DECT examination of breast tissue or breast cancer [24][25][26][27][28][29], and it is expected that the findings of the present study will encourage further advancement in DECT imaging and will help improve visualization of an IC in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 75%
“…Thus, the present study aimed to evaluate the utility of contrast-enhanced DECT for visualizing and evaluating an IC of breast cancer. Some previous studies have focused on DECT examination of breast tissue or breast cancer [24][25][26][27][28][29], and it is expected that the findings of the present study will encourage further advancement in DECT imaging and will help improve visualization of an IC in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 75%
“…A study 39 showed that DECT has limited potential for differentiating DCIS and Invasive Ductal Carcinoma. DECT does not have the capability to differentiate between DCIS and benign lesions, which is a diagnostic challenge that can be resolved through the use of MRI.…”
Section: Discussion and Prospectmentioning
confidence: 99%
“…In recent years, dual-energy CT has been used to characterize breast lesions. 22 This technique exploits the same physical principle of CESM. It can not only evaluate the effective uptake of contrast medium by the lesion but can also characterize tissue using z-analysis.…”
Section: Discussionmentioning
confidence: 99%